Balancing Athletic and Academic Excellence: A Quantitative Study of Student-Athletes' Time Management Strategies - Liu, Tianyue; Taresh, Sahar (Journal of Ecohumanism, 2024)
This study focuses on the unique challenges faced by student-athletes and explores how they find a balance between competitive sports and academic pursuits. Through a one-year longitudinal study of 360 college athletes from a variety of sports and academic backgrounds, we deeply analyzed the relationship between time management strategies and academic achievement, athletic performance, and psychological health. The study used quantitative research methods to analyze the data and revealed several key time management strategies that were associated with significant improvements in academic and athletic performance. In particular, we discovered a novel "flexible focus" strategy that enabled students to quickly switch their attention between learning and training while maintaining high efficiency. In addition, the study found the moderating effects of social media use, sleep patterns, and nutritional intake on time management effects. Based on these findings, we proposed a comprehensive "dual-track development model" to provide a practical guidance framework for student-athletes, coaches, and educators. This model is not only applicable to traditional college sports programs, but also considers the emerging field of e-sports, providing a new perspective for understanding and supporting the comprehensive development of student-athletes in the 21st century. The results of this study have important implications for higher education policy, athletic training program design, and the development of student support services, providing an empirical basis for promoting the comprehensive development of student-athletes.